Love and Organization Studies: Moving beyond the Perspective of Avoidance. Issue 7 (July 2019) - Tasselli, Stefano
Despite its undoubted centrality in modern society, Love has not received the attention it deserves in the study of organizations. Among the reasons for this avoidance is the fact that love is passionate and not authoritative; personal and subjective but not public. To understand the way organizational research can incorporate love, I explore and discuss three interweaving constructs. Eros (or a tale of the self ) calls for an expression of the individuality in organizations, in terms of creativity, sense making and experience. Philia (or a tale of trust ) contributes to explore trustworthy relationships, welcoming the other and enabling individuals to flourish in the workplace. Agape (or a tale of compassion ) refers to generalized love for humanity and opens to the understanding of compassionate leadership. In the discussion, I call for new directions in the study of love as the organization and the organization as love.